A modified cotton-wool column method for the rapid recovery of DNA from agarose gel slice - Liu, B.; Xu, W.; Luo, Z.; Liu, Q.
A previous report has described a simple and inexpensive cotton-wool column method for the recovery of DNA from agarose gel slice. However, it takes 2 h from start to finish. Here we present a simplified version of the technique which can cut hands-on time to within 20 min while retaining a fair DNA yield. Agarose gel slice was mashed before conducting centrifugation of the cotton-wool column tube, which enhanced DNA yield by at least 50 percent. Only one spin was required with a 30-35 percent DNA recovery rate, a second spin after treatment of agarose sediment in the tube with microwave would add another several percent. DNA obtained can be efficiently amplified by polymerase chain reaction (PCR)or subcloned. This provides a simple, rapid and cheap alternative to commercial kits. The mashed agarose gel slice alone or with water is used for centrifugation with the best efficiency. The flowthrough can be directly used for polymerase chain reaction (PCR)amplifications, which would only take less than 10 min to obtain. The flowthrough must be ethanol precipitated if other molecular manipulations such as cloning are to be conducted, which will require another 10 min. One sample costs around 1 US cent to process with the cotton-wool column method in developing countries. It will be a rapid and reliable alternative to expensive commercial kits.